Study on Monitoring System for Partial Discharge of Electrical Equipment - Miaofen Zhu; Guojin Chen; Ming Xu; Tingting Liu; Dong Xie; Yanping Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The detection and fault identification of the partial discharge is the important aspect for the monitoring of the power equipment. For the lacks of the traditional detection methods, this paper analyzed the UHF signal characteristic parameters of the power equipment’s partial discharge, and developed the UHF detection system of the partial discharge. The A/D technology of the gain equalization and quantization in the different bands is studied, and the fault diagnosis strategy of the partial discharge based on the UHF and AE is proposed. On the premise to ensure the integrity of the partial discharge signals, the acquisition, amplification, analysis and storage of the partial discharge signal is realized. The case-based reasoning technology determines the fault type and fault degree of the partial discharge to make the accurate judgment for the operational state of the equipment and improve the intelligence level and the operational reliability for the state diagnosis of the power equipment. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4327